When communication became a discipline - Eadie, William F. (Lexington Books, 2022)
"When Communication Became a Discipline describes how speech and journalism professors embraced the concept of communication as central to their scholarly work. It tells the story of how they transformed themselves and established an academic discipline of communication"--